lncRNAs and MYC: An Intricate Relationship - Iaccarino, Ingram (International journal of molecular sciences, 2017)
Long non-coding RNAs (lncRNAs) are emerging as important regulators of gene expression networks, acting either at the transcriptional level, by influencing histone modifications, or at the post-transcriptional level, by controlling mRNA stability and translation. Among the gene expression networks known to influence the process of oncogenic transformation, the one controlled by the proto-oncogene MYC is one of the most frequently deregulated in cancer. In B-cell lymphomas, the MYC gene is subject to chromosomal rearrangements that result in MYC overexpression. In many other cancers, the region surrounding MYC is subject to gene amplification. MYC expression is also controlled at the level of protein and mRNA stability. Neoplastic lesions affecting MYC expression are responsible for a drastic change in the number and the type of genes that are transcriptionally controlled by MYC, depending on differential promoter affinities. Transcriptome profiling of tumor samples has shown that several lncRNAs can be found differentially regulated by MYC in different cancer types and many of them can influence cancer cell viability and proliferation. At the same time, lncRNAs have been shown to be able to control the expression of MYC itself, both at transcriptional and post-transcriptional levels. Given that targeting the MYC-dependent transcriptional program has the potential to reach broad anticancer activity, molecular dissection of the complex regulatory mechanisms governing MYC expression will be crucial in the future for the identification of novel therapeutic strategies.